2021
DOI: 10.3390/nano11113153
|View full text |Cite
|
Sign up to set email alerts
|

Melting Enhancement in a Triple-Tube Latent Heat Storage System with Sloped Fins

Abstract: Due to the potential cost saving and minimal temperature stratification, the energy storage based on phase-change materials (PCMs) can be a reliable approach for decoupling energy demand from immediate supply availability. However, due to their high heat resistance, these materials necessitate the introduction of enhancing additives, such as expanded surfaces and fins, to enable their deployment in more widespread thermal and energy storage applications. This study reports on how circular fins with staggered d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As the PCMs have the inherent capability of high latent heat energy storage density, they also have low thermal conductivity, which reduces the heat transfer capability of either conduction or convection modes while charging and discharging the PCM. Several thermal conductivity enhancement methods have been introduced, such as metallic fins and foams ( Abdulateef et al, 2018 ; Mohammed et al, 2020 ; Mahmoud et al, 2021 ; Hashem Zadeh et al, 2022 ; Mohammed, 2022 ), metallic and carbon-based nanomaterials ( Arshad et al, 2020 ; Arshad et al, 2021b ; Kalidasan et al, 2022 ), heat pipes, and metallic matrices ( Eisapour et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…As the PCMs have the inherent capability of high latent heat energy storage density, they also have low thermal conductivity, which reduces the heat transfer capability of either conduction or convection modes while charging and discharging the PCM. Several thermal conductivity enhancement methods have been introduced, such as metallic fins and foams ( Abdulateef et al, 2018 ; Mohammed et al, 2020 ; Mahmoud et al, 2021 ; Hashem Zadeh et al, 2022 ; Mohammed, 2022 ), metallic and carbon-based nanomaterials ( Arshad et al, 2020 ; Arshad et al, 2021b ; Kalidasan et al, 2022 ), heat pipes, and metallic matrices ( Eisapour et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the most significant inconsistency that almost all PCMs today suffer from is their intrinsically low heat conduction, which has a negative impact on the system’s thermal reaction to the cyclic heat charging/discharging operations. To overcome this issue, researchers identified different approaches for the thermal enhancement of TES systems, such as porous matrices [ 16 , 17 , 18 , 19 ], extended fins [ 20 , 21 , 22 , 23 , 24 , 25 ], and heat pipes [ 26 , 27 ] along with utilizing good performing casing for PCM containment. Boosting the thermal performance of PCM-based storage devices by applying extended fins to the tubes transporting the heat-transfer fluid (HTF) is often considered as one of the most effective enhancement methods in energy storage systems [ 23 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that this method leads to up to 15% energy saving compared to the conventional insulation techniques. Mahmoud et al [ 11 ] worked on the melting enhancement of RT-35 wax in a triple-tube (TT) unit with sloped circular fins. They evaluated the influence of fins with various sizes and orientations with the same fin volume fractions.…”
Section: Introductionmentioning
confidence: 99%